Evaluating and Reconceptualizing the Pancasila Student Profile: A Critical Analysis of Value Alignment and Character Education in the Merdeka Curriculum - Miftakhul Arif (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to evaluate the validity of the Pancasila Student Profile as a character assessment framework by examining its alignment with the foundational values of Pancasila. Methodology: This qualitative study employed library research and limited field inquiry. Data were collected through document analysis and semi-structured interviews. The evaluation was conducted using qualitative content analysis based on four indicators: philosophical consistency, value representation, conceptual coherence, and educational applicability. Triangulation was used to enhance the credibility of the findings. Main Findings: The evaluation revealed that several core values of Pancasila, particularly humanity, unity, and social justice, are not explicitly represented in the current six dimensions of the Pancasila Student Profile. The findings also indicate an overemphasis on project-based implementation. Based on these results, a five-value framework and an integrated character education model emphasizing internalization, habituation, and contextual application were developed. Novelty/Originality of this study: This study introduces a conceptual evaluation framework for assessing the alignment between educational value constructs and national philosophical foundations. It offers a reconceptualized Pancasila Student Profile rooted in the original five principles of Pancasila and proposes an integrated model that extends character education beyond project-based learning toward sustainable value formation and assessment practices.